Screening of Active Compounds from Sargassum Seaweed Collected from Lampung Bay - Handayani, Muliawati; Nuzapril, Mulkan; Setya, Dona; Putri, Aprilia Syah (ABEC Indonesia, 2024)
Sargassum is a genus of brown algae with significant potential as a bioprospecting material. This seaweed isabundant in Lampung Bay, although it has not yet received the same attention as commercial seaweeds like Gracilaria sp.and Eucheuma sp. The purpose of this study is to inventory the types of active compounds in Sargassum extracts usingsolvents with different polarities. Extraction was carried out using the maceration method with methanol (polar) and nhexane (non-polar) solvents in a 1:3 ratio. Methanol yielded a more optimal quantity and concentration of filtratecompared to n-hexane. Qualitative testing of active compounds was conducted through phytochemical assays, indicatingthe presence of flavonoids, alkaloids, polyphenols/tannins, and saponins in Sargassum. The target flavonoid compoundwas confirmed by quantitative analysis using UV-Vis spectrophotometry, which revealed a flavonoid content of 7.84grams in the methanol-solvent sample and 3.61 grams in the n-hexane sample. To support its use in aquacultureactivities, further testing for antibacterial activity is required.